The additional yield of GeneXpert MTB/RIF test in the diagnosis of pulmonary tuberculosis among household contacts of smear positive TB cases. (August 2016) - Habte, Dereje; Melese, Muluken; Hiruy, Nebiyu; Gashu, Zewdu; Jerene, Degu; Moges, Feleke; Yifru, Sisay; Girma, Belaineh; Kassie, Yewulsew; Haile, Yared Kebede; Suarez, Pedro Guillermo; Tessema, Belay
Highlights: GeneXpert identified TB cases 3 times that of the cases identified by ZN microscopy GeneXpert helped in identifying rifampicin resistant TB among index cases GeneXpert test was done using a single sample unlike 3 in ZN microscopy Abstract: Objective: The objective of this study was to compare the diagnostic yield of GeneXpert MTB/RIF with Ziehl-Neelson (ZN) sputum smear microscopy among index TB cases and their household contacts. Methods: A cross sectional study was conducted among sputum smear positive index TB cases and their household contacts in Northern Ethiopia. Results: Of 353 contacts screened, 41 (11%) were found to have presumptive TB. GeneXpert test done among 39 presumptive TB cases diagnosed 14 (35.9%) cases of TB (one being rifampicin resistant), whereas the number of TB cases diagnosed by microscopy was only 5 (12.8%): a 64.3% increased positivity rate by GeneXpert versus ZN microscopy. The number needed to screen and number needed to test to diagnose a single case of TB was significantly lower with the use of GeneXpert than ZN microscopy. Of 119 index TB cases, GeneXpert test revealed that 106 (89.1%) and 5 (4.2%) were positive for rifampicin sensitive and rifampicin resistant TB, respectively. Conclusion: GeneXpert test led to increased TB case detection among household contacts in addition to its advantage in the diagnosis of Rifampicin resistance among contacts and index TB cases. There should be a consideration in using GeneXpert MTB/RIF as a point of care TB testing tool among high risk groups.